Description of a new branchiate scale-worm (Polychaeta: Polynoidae) from the hydrothermal vent on Southwest Indian Ocean Ridge - Zhou, Yadong; Zhang, Dongsheng; Lu, Bo; Wang, Chunsheng (Zootaxa, 2017)
During the Dive90 and Dive94 of Chinese manned submersible “Jiaolong”, some polychaete specimens were collected from the “Longqi” vent field on the Southwest Indian Ocean Ridge. A new species belonging to the genus Branchipolynoe, Branchipolynoe longqiensis n. sp., is described in this study. It can be easily distinguished from congeners by its biramous parapodia with relatively reduced notopodia, stout notosetae and branchiae with short terminal filaments.